Use of TRNSYS for modelling and simulation of a hybrid pv–thermal solar system for Cyprus - Kalogirou, Soteris A. (My University, 2001)
This paper deals with the modelling and simulation of a hybrid photovoltaic–thermal (PV/T) solar energy system. This is a combined system consisting of a normal PV panel at the back of which a heat exchanger with fins is embedded. The advantage of this type of system is that the PV panel operates at a lower temperature, thus more efficiently, and also hot water is produced at the same time as electricity. The PV system consists of a series of PV panels, a battery bank and an inverter whereas the thermal system consists of a hot water storage cylinder, a pump and a differential thermostat. The system is modelled using TRNSYS, which is a transient simulation program and typical meteorological year (TMY) conditions for Nicosia, Cyprus. The main component of the TRNSYS deck file constructed for this purpose is Type 49, accompanied by other additional components required for the model. The results show that the optimum water flow rate of the system is 25 l/h. The hybrid system increases the mean annual efficiency of the PV solar system from 2.8% to 7.7% and in addition covers 49% of the hot water needs of a house, thus increasing the mean annual efficiency of the system to 31.7%. The life cycle savings of the system is Cy£790.00 and the pay-back time is 4.6 years.
Keywords: Solar energy system; Hybrid Photovoltaic/Thermal (PV/T)